2011
DOI: 10.1158/0008-5472.can-10-2100
|View full text |Cite
|
Sign up to set email alerts
|

Ron Kinase Transphosphorylation Sustains MET Oncogene Addiction

Abstract: Receptors for the scatter factors HGF and MSP that are encoded by the MET and RON oncogenes are key players in invasive growth. Receptor cross-talk between Met and Ron occurs. Amplification of the MET oncogene results in kinase activation, deregulated expression of an invasive growth phenotype, and addiction to MET oncogene signaling (i.e., dependency on sustained Met signaling for survival and proliferation). Here we show that cancer cells addicted to MET also display constitutive activation of the Ron kinase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 49 publications
1
73
0
Order By: Relevance
“…Crosstalk between c-MET and other RTKs has also been studied in great depth because of its potential importance in the development of [Benvenuti et al 2011]. Recently, transactivation between c-Met and both platelet-derived growth factor receptor (PDGFR) and Axl was found to play a role in bladder cancer [Yeh et al 2011].…”
Section: Hgf/c-met Signalingmentioning
confidence: 99%
“…Crosstalk between c-MET and other RTKs has also been studied in great depth because of its potential importance in the development of [Benvenuti et al 2011]. Recently, transactivation between c-Met and both platelet-derived growth factor receptor (PDGFR) and Axl was found to play a role in bladder cancer [Yeh et al 2011].…”
Section: Hgf/c-met Signalingmentioning
confidence: 99%
“…Several kinase inhibitors such as imatinib and geftinib have been very successful in the clinics due to the phenomenon of oncogene addiction. Recently it is shown that cross-talk between RON and MET sustains the oncogene addiction of MET [69]. Thus study of the phenomenon of oncogene addiction with reference to RON activation in colon cancer will further strengthen the avenues for therapeutic utilization of RON RTK.…”
Section: Future Directionsmentioning
confidence: 97%
“…RON and Met concomitant overexpression is detected in many tumor types. 65,68 Lee et al 66 found that overexpression of RON and c-Met in CRC is associated with a remarkably poor clinical outcome and short-term disease-free survival. Various mechanisms underlay on abnormal expression and activation of c-Met and RON such as gene amplification, enhanced TK activity due to point mutations, and aberrant splicing of RON.…”
Section: C-met and Ron Receptorsmentioning
confidence: 99%
“…c-Met and RON signaling pathways mostly rely on activation of PI3K and MAPK as key adaptor proteins which result in PI3K/AKT, Src, STAT3, NF-κB, FAK, and β-catenin activation, leading to critical cellular responses including cytoskeletal changes, EMT, stemness, invasion, resistance to apoptosis, angiogenesis, and proliferation. 64 Benvenuti et al 65 …”
Section: C-met and Ron Receptorsmentioning
confidence: 99%